Private Contracting, Law and Finance - Acheson, Graeme G; Campbell, Gareth; Turner, John D (Review of Financial Studies, 2019)
In the late nineteenth century Britain had almost no mandatory shareholder protections, but had very developed financial markets. We argue that private contracting between shareholders and corporations meant that the absence of statutory protections was immaterial. Using approximately 500 articles of association from before 1900, we code the protections offered to shareholders in these private contracts. We find that firms voluntarily offered shareholders many of the protections that were subsequently included in statutory corporate law. We also find that companies offering better protection to shareholders had less concentrated ownership. Received August 19, 2016; editorial decision October 24, 2018 by Editor David Denis. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.